The Influence of Social Support, Community Resilience, and Coping Strategies on Community Preparedness for Flood Disasters - Permana, Iwan (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: The objective of this study was to investigate the impact of social support, community resilience, and coping techniques on preparedness, as well as the concurrent influence of social support, community resilience, and coping strategies on preparedness. Methods: This study uses a correlational design with a cross-sectional approach. The study population was 1,538 people, and a sample of 317 people with a proportional random sampling technique. Instruments used in this study are LIPI-UNESCO, Multidimensional Scale of Perceived Social Support (MSPSP), Connor-Davidson Resilience Scale (CD-RISC), and Ways of Coping Questionnaire (WCQ), data analysis using linear regression. Results: Most social support was moderate, at 45.7%; community resilience was moderate, at 50.2%; coping strategies were high, at 50.8%; and preparedness was ready, at 36.9%. There is an influence of social support, community resilience, and coping strategies on preparedness (p-value <0.05). Social support, community resilience, and coping strategies have a simultaneous influence on preparedness (p-value <0.05). Conclusion: Social support, community resilience, and coping strategies simultaneously influence preparedness.